Troponin trends during anthracycline chemotherapy and their correlation with cardiovascular risk scores. (25th November 2020) - Mallouppas, M; Chung, R; Macklin, A; Ghosh, A; Yellon, D.M; Walker, J.M
Abstract: Background: Anthracycline cardiotoxicity has been known for many years but identifying patients most at risk remains imperfect. Conventionally, standard cardiovascular risk factors including biomarkers are included in assessments. Purpose: We investigated serial troponin T (Tn-t) values during anthracycline chemotherapy and correlated these with baseline patient risk factors using a validated cardiovascular risk assessment tool (QRISK3). Methods: 52 patients from the ERIC-ONC study had their QRISK3 score calculated using https://qrisk.org/. ERIC-ONC (Effect of Remote Ischaemic Conditioning in ONCology) is an ongoing double-blind randomised sham-controlled study in patients receiving anthracyclines, with high sensitivity Tn-t taken before and after (within 24 hrs) each chemotherapy cycle. Results: Mean age was 50±16 (range 22–80) with 42% females. Mean QRISK3 score was 6.9±7.3% (range 0.1–33.4%). 53% were non-smokers and 27% ex-smokers. 77% had no family history of premature coronary disease. 8% had hypertension and 2 patients had diabetes. Mean Tn-t at each cycle (baseline to cycle 6) was 8ng/L (n=51, range <3–45ng/L), 10ng/L (n=50, <3–48ng/L), 12ng/L (n=50, <3–45ng/L), 16ng/L (n=39, <3–64ng/L), 24ng/L (n=35, 5–99ng/L) and 32ng/L (n=33, 3–67ng/L) (Figure). Mean Tn-t at one month post chemotherapy was 39ng/L, (n=40, 5–128ng/L). There was a significant increase in Tn-t by cycle 6 (mean difference 25ng/L compared to baseline, p<0.001) that persisted one month after chemotherapy (mean difference 32ng/L compared to baseline, p<0.001). Tn-t was more commonly positive (i.e.>14ng/L) with each successive cycle (10% at baseline vs 73% at cycle 6). Tn-t remained positive in 75% of cases at one month. There was a moderate positive correlation (ρ=0.464, p=0.001) between QRISK3 and baseline Tn-t that became stronger by cycles 4 and 5 (cycle 4 ρ=0.555, p<0.001, cycle 5 ρ=0.618, p<0.001). At one month follow up, correlation was weaker but still present (ρ=0.513, p=0.001). Correlation of QRISK3 with troponin difference from baseline (ΔTn-t) was moderately positive only in the later cycles (ΔTn-t-cycle-3 ρ=0.25, p=0.09, ΔTn-t-cycle-5 ρ=0.521 p=0.001) and remained positive at one month post chemotherapy (ρ=0.445, p=0.005). Samples taken after each cycle (median=108 minutes for 127 samples) were not significantly different to the pre-chemotherapy levels at each cycle with a mean reduction in Tn-t of 0.82ng/L for cycle 1 (p=0.12), 1.83ng/L for cycle 2 (p=0.001), 2.36ng/L for cycle 3 (p=0.002), 1.58ng/L for cycle 4 (p=0.119), 2.58ng/L for cycle 5 (p=0.001) and 2.35ng/L for cycle 6 (p=0.101). Conclusion: Troponin values increase during chemotherapy with anthracyclines and remain elevated one month after chemotherapy. QRISK3 strongly correlates with Tn-t elevations during later chemotherapy cycles and early post chemotherapy, and may be useful to identify patients at risk of cardiotoxicity. Subsequent analysis will reveal if these elevations affect clinical outcomes. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): UCH Charitable Trust Rosetrees Foundation